Study of the Effect of Planting Date and Plant Density on Some Morphological and Physiological Traits of Forage Maize (Zea mays L.) under the Conditions of Jableh Plain (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Biological Sciences Series, 2026)
The research was conducted in Al-Eidiya village, Jableh region / Lattakia Governorate, during the 2024 agricultural season, with the aim of studying the effect of sowing date and plant density on some morphological and physiological traits of three maize hybrids: the Russian hybrid Krasnodarski 291, the local hybrid Dahab 100, and the hybrid Ghota 82. Two sowing dates were tested: April 1 and July 25, and three plant densities were applied: 83,333 plants/ha, 66,666 plants/ha, and 55,555 plants/haThe studied traits included: plant height, number of leaves per plant, height of the first ear, and leaf area. Results: The hybrid Ghota 82 outperformed the others in most studied traits, with mean values of: Plant height: 215.49 cm, Number of leaves: 15.22 leaves/plant, First ear height: 105.22 cm, Leaf area: 10,758.21 cm². The first sowing date (April 1) gave the highest averages: Plant height: 202.61 cm, Number of leaves: 12.29 leaves/plant, First ear height: 85.81 cm, Leaf area: 9,381.39 cm². The third plant density (55,555 plants/ha) was superior in most traits, with averages of: Plant height: 201.36 cm, Number of leaves: 12.33 leaves/plant, First ear height: 85.23 cm Leaf area: 8,997.29 cm²
Keywords: Mize, Zea mays L., Planting Date, Plant Density.